Preparation for family-school partnerships within initial teacher education programmes in England. Issue 3 (27th May 2018) - Mutton, Trevor; Burn, Katharine; Thompson, Ian
Abstract: The few studies conducted in Europe to date suggest that little attention is paid to pre-service teacher preparation for family-school partnerships (FSP) and that many teachers feel unprepared for such work. In England there has been little research in this area but a government review of best practice in parental involvement with schools concluded that '(t)eachers often lack the confidence and knowledge to work with parents …'. Given the apparent discrepancy between the need for teachers to be more knowledgeable about FSP and the lack of opportunity within initial teacher education (ITE) programmes to address the issues, we carried out a national survey of ITE providers in England in order to ascertain what provision is currently on offer. Our findings indicate that while there is overall recognition of the value of preparing trainee teachers to become confident and knowledgeable about home-school partnerships, ITE providers feel constrained by the lack of time available to them to explore this area in greater detail. The article concludes by discussing some of the challenges of both planning and delivering effective FSP provision within the ITE curriculum and how this might relate to future professional learning.